IOT-Based Smart Energy Management for Sustainable Operational Efficiency in the Industry 4.0 Era - Diana Magfiroh; Elvira Fitriyanti (Worldwide Research Publishing, 2026)
This study aims to evaluate the contribution of IoT-based smart energy management towards operational efficiency and sustainability of manufacturing systems in the context of Industry 4.0. Using a quantitative correlational design, data were collected from 100 professional respondents in the manufacturing sector through questionnaires and structured interviews. Statistical analysis was performed using Pearson correlation, linear regression, t-test, and ANOVA with the help of SPSS software. The results showed a very strong and significant relationship between the use of IoT-based smart energy management systems and energy efficiency (r = 0.849), operational efficiency (r = 0.706), and environmental sustainability (r = 0.774). Linear regression showed that the use of the technology explained 72.1% of the variability in energy efficiency (R² = 0.721; p < 0.001). The ANOVA results also showed significant differences between groups of technology users in terms of efficiency achievements. These findings indicate that IoT-based smart energy management can be an important strategy in digital transformation and more sustainable industrial decision-making. This study contributes to developing smart-manufacturing energy theory and provides practical implications for industrial management in implementing adaptive, connected, and environmentally friendly energy systems.